Indonesian economic performance on trade and investment after Asean economic community - Husnan, Lalu Hamdani; Jufri, Akhmad; Manan, Abdul; Irwan, M.; Wahyunadi, Wahyunadi (Edelweiss Applied Science and Technology, 2024)
Indonesia has been signed to participate on ASEAN Economic Community since 7 October 2003, at the ninth ASEAN Summit in Bali. This included an ASEAN Economic Community ‘a single market and production base with free flow of goods, services and skilled labor and freer flow of capital by 2020’. There is much economic progress has been achieved mutually during last decade of this economics community. This economics community seems to be inspired by previous summit about ASEAN free trade area on 1992. This paper examines the Indonesian present trade and investment after joining ASEAN Economics Community and implementing CEPTs, and analyses further the impact of those community/CEPTs on Indonesian trade and investment performance. It was utilized the data on Indonesian exports to and imports from ASEAN countries as well Indonesian invests to and invests from ASEAN countries. The results clearly shown that Indonesian performed well and gained much benefit from this economic community/CEPTs especially in its comparative advantage industry.